Combined Working Memory Training and Transcranial Magnetic Stimulation Demonstrates Low Feasibility and Potentially Worse Outcomes on Delay to Smoking and Cognitive Tasks: A Randomized 2 × 2 Factorial Design Pilot and Feasibility Study. Issue 12 (30th July 2022) - Lechner, William V; Philip, Noah S; Kahler, Christopher W; Houben, Katrijn; Tirrell, Eric; Carpenter, Linda L
Abstract: Introduction: Repetitive Transcranial Magnetic Stimulation (rTMS) has shown promising results in treating several Substance Use Disorders including Tobacco Use Disorder. However, questions remain regarding how to optimize treatment outcomes. Enhancement of working memory by rTMS is a potential therapeutic mechanism. The current pilot study examined whether rTMS plus a cognitive training program could enhance the effects of rTMS on smoking behaviors using a controlled, factorial design. Aims and Methods: We hypothesized that cognitive training plus stimulation would improve control over smoking behaviors, resulting in enhanced cognitive performance and increased latency to smoke on a delay to smoking analog task. Using a 2 × 2 factorial design, nicotine dependent smokers ( n = 43) were randomized to receive 10 sessions of active (10 Hz) or sham rTMS delivered to the left dorsolateral prefrontal cortex, plus active or sham working memory training (WMT) prior to and following stimulation. Results: Contrary to hypotheses, we observed a significant interaction effect, indicating that combining the two active interventions (rTMS+WMT) resulted in worse performance on the smoking analog task (B = −33.0, 95% CI = −64.39, −1.61, p < .05), compared to delivering either intervention alone. Additionally, although active rTMS (compared to sham rTMS) improved letter-sequencing performance (B = 1.23, 95% CI = 0.08–2.38, p < .05), and active WMT (compared to sham WMT) improved back-digit task performance (B = 1.53, 95% CI = 0.02–3.05, p < .05), combining interventions worsened the effect of each on a back-digit task (B = −3.01, 95% CI = −5.96, −0.052, p < .05). Conclusions: These preliminary findings indicate potential iatrogenic effects of combining rTMS and this working memory training intervention and underscore the need for rigorous evaluation of substance specific conceptual frameworks when selecting future combination interventions. Implications: Counter to hypothesis, this study found no additional benefit of adding a working memory training program to a rTMS protocol in a sample of daily smokers. The combination condition (active rTMS + active training) resulted in worse performance on a delay to smoking analog task and a measure of working memory performance compared to delivering either intervention alone. These preliminary findings inform strategies for optimizing rTMS in smokers and highlight the need for future studies to consider several key components of candidate combination interventions, including effects on regulation of substance use. Clinical Trial Registration (if any): The trial was registered at ClinicalTrials.gov (NCT03337113).